Integrated model for implementing knowledge management - Castillo, Lucio Abimael Medrano; Cazarini, Edson Walmir (Revista Gestão da Produção Operações e Sistemas, 2012)
Knowledge has become the most important strategic resource in the current environment of high competition, a source of sustainable competitive advantage. Due to its importance in organizational success, managing it properly is a major concern of executives. To this goal models and methodologies have been developed to implement knowledge management in companies, researches that have limitations and lead organizations to failed attempts, limitations as the excessive orientation on the information technologies, the lack of alignment with organizational strategy, the lack of attention on human and cultural factors, the development of models without methodological basis, and mainly, an divided approach of the implementation of knowledge management. Based on these limitations, this study aims to develop an integrated model for the implementation of knowledge management, using the EKD modeling methodology. To achieve the goal we developed a literature search, generated the first version of the model, validated it with experienced professionals, and ultimately improved it. The work resulted in a systemic and integrated model for the implementation of knowledge management that can guide organizations in this practice and serve as a reference for its better understanding.Keywords: Knowledge Management, Organizational Modeling; EKD.